1994
DOI: 10.1016/0014-5793(94)00090-5
|View full text |Cite
|
Sign up to set email alerts
|

Thiol dependent isomerization of all‐trans‐retinoic acid to 9‐cis‐retinoic acid

Abstract: The important biological effector 9-cis-retinoic acid can be generated by liver microsomes or by bovine serum albumin in detergent. The mechanism of this isomerization reaction is the subject of these studies. The protein mediated isomerization process is shown to be thiol-and pH-dependent. Moreover, the retinoic acids are also isomerized by 1-dodecanethiol in the presence of detergents. This isomerization process is pH-dependent as well, with isomerization rates increasing with pH. The isomerization reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…The isomerization was found to be nonsaturable, nonstereo specific, blocked by thiol-blocking reagents like N-ethylmaleimide and therefore likely to be thiol dependent (Urbach and Rando, 1994a). Similar effects were later demonstrated with glutathione (Shih et al, 1997;Jewell and McNamara, 1990), albumin, as well as in mixtures of SDS and 1-dodecanthiol alone (Urbach and Rando, 1994a). Lanvers et al, 1996 demonstrated that cell culture medium with 10% heat-deactivated FCS alone isomerizes single isomers of RA into a mix of isomers.…”
Section: Artifacts Generated During Sample Handling and Extractionmentioning
confidence: 78%
“…The isomerization was found to be nonsaturable, nonstereo specific, blocked by thiol-blocking reagents like N-ethylmaleimide and therefore likely to be thiol dependent (Urbach and Rando, 1994a). Similar effects were later demonstrated with glutathione (Shih et al, 1997;Jewell and McNamara, 1990), albumin, as well as in mixtures of SDS and 1-dodecanthiol alone (Urbach and Rando, 1994a). Lanvers et al, 1996 demonstrated that cell culture medium with 10% heat-deactivated FCS alone isomerizes single isomers of RA into a mix of isomers.…”
Section: Artifacts Generated During Sample Handling and Extractionmentioning
confidence: 78%
“…Therefore, the data obtained in dose-response experiments indicate that increased expression of GLUT4 in response to retinoic acids could very well be mediated by RARs, as RARs are activated by either all-trans or 9-cisRA. However, in the presence of biological membranes, atRA can be partially isomerized to 9-cisRA [37]. Thus, based on the dose-response data we could not rule out that atRA was partially isomerized to 9-cisRA and that only RXRs were involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results argue against this, and it is more likely that the all-transretinoic acid/retinol that originated from all-trans-␤-carotene is isomerized to the 9-cis form. It has been reported that alltrans-retinoic acid can be isomerized to 9-cis-retinoic acid by thiolate radicals (44,45). Another study suggests that an isomerase converts all-trans-retinol to 9-cis-retinol (46).…”
Section: Discussionmentioning
confidence: 99%